Death at Sea: The McCraken Family and their Losses Aboard the Steamship Arctic - Robinson, Al (2004)
Report prepared as part of the coursework required for REL 167, Speaking Stones. Description and interpretation of the monument to the McCraken family, and a description of the events leading to the loss of the steamship Arctic in 1854.